Prevalence of tinnitus in workers exposed to noise and organophosphates - Delecrode, Camila Ribas; de Freitas, Thais Domingues; Frizzo, Ana Claúdia Figueiredo; Cardoso, Ana Claúdia Vieira (International Archives of Otorhinolaryngology, 2012)
Introduction: Research on the workplace has emphasized the effects of noise exposure on workers' hearing, but has not considered the effects of agrochemicals.Aim: To evaluate and correlate the hearing level and tinnitus of workers exposed simultaneously to noise and organophosphates in their workplace and to measure tinnitus distress on their quality of life.Method: A retrospective clinical study. We evaluated 82 organophosphate sprinklers from the São Paulo State Regional Superintendence who were active in the fight against dengue and who were exposed to noise and organophosphates. We performed pure tone audiometry and applied the translated THI (Tinnitus Handicap Inventory) questionnaire.Results: Of the sample, 28.05% reported current tinnitus or had presented tinnitus, and the workers with tinnitus had an increased incidence of abnormal audiometry. The average hearing threshold for the 4–8-kHz frequency range of the workers with current tinnitus was higher than that of the others, and was most affected at the 4-kHz frequency. The THI score ranged 0–84, with an average score of 13.1. Twelve (52.17%) workers had THI scores consistent with discrete handicap.Conclusion: There is an increased incidence of abnormal pure tone audiometry in workers with tinnitus, and its impact on the workers' quality of life was discrete. The correlation between average hearing threshold and tinnitus distress was weak.
Keywords: occupational health; hearing; tinnitus; questionnaires; noise; insecticides; organophosphates